Financial distress prediction in Nigerian oil and gas industry: a multivariate approach (Journal of Economic Research & Business Administration, 2022)
The oil and gas sector are in no doubt a very sensitive and equally a very important sector and majorlythe main stay of Nigerian economy. Recent dropped in the prices of oil in the international marketis of great concerned to all oil producing and exporting countries of which Nigeria is a major player.Colossal cost implications of collapsed business are enormous, detrimental, anti-economic growth anddevelopment but preventable if the early warning distress signals can be predicted. Thus, this studypredicts financial distress in Nigeria oil and gas firms using multivariate approach. Longitudinal designwas adopted for the study. Data were extracted from Nigeria Stock Exchange (NSE) fact books from year2000 to 2018. Information obtained were arranged and collated in ratio analysis. Multiple discriminantanalysis (MDA) was used to predict the early warning signals and post-prediction differences were testedusing t-test. The prediction results revealed the failure early warning signals in the study area to be earningbefore interest and tax (EBIT), working capital (WCA), and TAR with strong prediction accuracy. Thestudy concluded that Nigerian oil and gas companies are susceptible to failure given the early warningsignals identified. It is recommended that the sampled firms should take into cognizance the identifiedearly warning signals to prevent financial distress and take preventive measures towards rejuvenation.Key words: Early warning signals, financial distress prediction, MDA, oil and gas firms, rejuvenation.